Mating Enhances Expression of Hormonal and Trophic Factors in the Midbrain of Female Rats - Frye, Cheryl A.; Chittur, Sridar V. (Frontiers in Behavioral Neuroscience, 2020)
Abstract Among female rats, mating enhances neurosteroid formation in the midbrain ventral tegmental area (independent of peripheral steroid-secreting glands, the ovaries and adrenals). The sources/targets for these actions are not well-understood. In Experiment 1, proestrous rats engaged in a mating paradigm, or did not, and had midbrains assessed via Affymetrix rat genome microarrays. In Experiment 2, the influence of gonadal and adrenal glands on the expression of these genes was assessed in rats that were proestrous, ovariectomized (OVX), or OVX and adrenalectomized (ADX). Microarrays revealed 53 target genes that were significantly up-regulated (> 2.0-fold change) in response to mating. Mating significantly enhanced midbrain mRNA expression of genes involved in hormonal and trophic actions: Gh1, S100g, and Klk1b3 in proestrous, but not OVX and/or ADX, rats; Fshb in all but OVX/ADX rats; and Lhb and Tshb in all rats. Thus, mating enhances midbrain gene expression, independent and dependent of, peripheral glands.